2020
DOI: 10.46483/deuhfed.634402
|View full text |Cite
|
Sign up to set email alerts
|

Kemoterapi ve Radyoterapi Alan Hastalarda Oral Mukozit: Bir Gözden Geçirme

Abstract: ÖzOral mukozit, kemoterapi ve/veya radyoterapiyi takiben oral mukoza bütünlüğünün bozulmasıyla ortaya çıkmaktadır. Özellikle baş-boyun bölgesine uygulanan radyoterapi, antimetabolit ve alkilleyici kemoterapi ajanları oral mukozit sıklığında ve şiddetinde artışa neden olmaktadır. Oral mukozit gelişen hastalarda ağız/boğazda ağrı, enfeksiyon ve kanama gibi ciddi komplikasyonlar ortaya çıkmaktadır. Ayrıca günlük yaşam aktivitelerinde bozulma, sıvı, besin ve analjezi desteği, hastanede yatış süresinin uzaması ve t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…It has been observed that oral mucositis frequently occurs in patients after radiotherapy, which is one of the treatments in which radiation is used intensively [5]. Mucositis can cause mouth ulcers, pain and inflammation in the oral tissues.…”
Section: Evaluation Of Radiation Exposure Of the Oral Cavity In C-arm...mentioning
confidence: 99%
“…It has been observed that oral mucositis frequently occurs in patients after radiotherapy, which is one of the treatments in which radiation is used intensively [5]. Mucositis can cause mouth ulcers, pain and inflammation in the oral tissues.…”
Section: Evaluation Of Radiation Exposure Of the Oral Cavity In C-arm...mentioning
confidence: 99%